2019
DOI: 10.11648/j.wjap.20190402.12
|View full text |Cite
|
Sign up to set email alerts
|

Complex Dynamics of the Chua’s Circuit System with Adjustable Symmetry and Nonlinearity: Multistability and Simple Circuit Realization

Abstract: Background: Since the invention of Chua's circuit, numerous generalizations based on substitution of the nonlinear function have been reported. One of the generalizations is obtained by replacing the piecewise-linear with the cubic and/or quadratic polynomial. These nonlinearities are used to be implement using analog multipliers which are relatively expensive. In this realization we propose a different approach to synthetize both cubic and quadratic nonlinearities of empirical Chua's circuit. Methods: The ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…In particular, the authors in [5] found a coexistence limit cycle and symmetric hidden attractors in the Chua system. It was shown in [6] that a modified Chua system can display complex dynamics behaviors of symmetric and asymmetric coexisting attractors. In this paper, we study the following Chua system described by the differential equations ẋ = a(z…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
“…In particular, the authors in [5] found a coexistence limit cycle and symmetric hidden attractors in the Chua system. It was shown in [6] that a modified Chua system can display complex dynamics behaviors of symmetric and asymmetric coexisting attractors. In this paper, we study the following Chua system described by the differential equations ẋ = a(z…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
“…In our study, such trajectories show chaotic motions. The multistability feature [70]- [72] is exhibited by a perturbed DS when there exist two or more dynamic properties such as chaos, quasiperiodic, periodic and multiperiodicity for same set of parameters but distinct initial conditions. Secure Hash Algorithm 512 (SHA−512) is one of the prominent solutions to withstand various forms of attacks in cryptography given than it is not reversible [73].…”
Section: Multistability Propertymentioning
confidence: 99%
“…Recently many research works have been proposed to study the dynamical properties of chaotic systems and have been exploited for image encryption [36] , [37] . For instance, Xu et al [38] presented a scheme based on bit-level swapping permutation and diffusion.…”
Section: Related Workmentioning
confidence: 99%